MARINE FISHERIES RESOURCES IN THE 20 AND 40 METRE REGIONS OFF THE GOA COAST - Prabhu, M S; Dhawan, Rajinder M (Indian Journal of Fisheries, 2011)
Experimental fishing carried out in the 20 and 40 metre regions at 10 stations along the Goa coast has revealed that the shallower regions are comparatively more productive than the deeper regions except at Terekhol in the northern zone. Comparing the density of fish populations in the northern, central and southern zones, it has heen noticed that the central zone is richer than the others. An increase in the catch rate from the south to north was discemable in the 40 metre depth and from the north to south in the 20 metre areas. A study of the catch composition has indicated that the much sought after shrimps have maximum concentration in the central zone where they formed 25.88^ and 8.43% in the 20 and 40 metre areas respectively. The distribution of important species on depthwise, stationwise and monthwise basis has been dealt with. The peak period for the prawn fishing is from December to February. The estimated yield per boat per day at different stations has been indicated. Certain guidelines for the future course of investigations have been suggested.